The relationship of competition anxiety with the performance of the kinematic chain in the rhythmic gymnastics of the third year student’s collage of physical Education and sports science at the University of Baghdad - Abdul aziz muhsen, Tamadher; Adnan Mohammed Ameen, Ban; jasem mohammed hasan, Wasan (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the level of anxiety of female students as well as its relationship to their scores in the Kinetic Chains Exam in Rhythmic Gymnastics. The researcher used the descriptive approach to suit his research procedures and the results he wanted. The researcher used data on the third-year students group at the College of Physical Education and Sports Science/University of Baghdad, and there were (87) students distributed among three groups. (6) students were excluded because they did not show up on the day of conducting the anxiety test and the exam in the movement chains in rhythmic gymnastics. Thus, the sample has become 811 students, representing 93% of the research community. The researcher has used the competition anxiety scale prepared by (Rainer Martins) and translated by (Allawi). The researchers concluded in their study that by increasing the grades that students obtain in performing motor chains using collar and rope, the degree of anxiety decreases. They also found that there is a relationship between the grades that they got in the hoop and in the rope. The degrees of the research sample in anxiety were at a high level by more than 50%, and this is considered a dangerous indicator that teachers and trainers must pay attention to and try to treat and reduce.